Bivalent Vaccine Effectiveness Against Type-Specific HPV Positivity: Evidence for Cross-Protection Against Oncogenic Types Among Dutch STI Clinic Visitors. (11th November 2017) - Woestenberg, Petra J; King, Audrey J; van Benthem, Birgit H B; Donken, Robine; Leussink, Suzan; van der Klis, Fiona R M; de Melker, Hester E; van der Sande, Marianne A B; Hoebe, Christian J P A; Bogaards, Johannes A; ,
Abstract : In this cross-sectional study among vaccine-eligible female sexually transmitted infection clinic visitors, high vaccine effectiveness of the bivalent vaccine against the vaccine types HPV-16/18 was demonstrated and significant cross-protection against the nonvaccine high-risk HPV types 45, 35, 31, and 52. Abstract: Background: Observational postmarketing studies are important to assess vaccine effectiveness (VE). We estimated VE from the bivalent human papillomavirus (HPV) vaccine against HPV positivity of vaccine and nonvaccine types in a high-risk population. Methods: We included all vaccine-eligible women from the PASSYON study, a biennial cross-sectional survey in Dutch sexually transmitted infection clinics. Vaginal swabs were analyzed using a polymerase chain reaction-based assay (SPF10 -LiPA25 ) able to detect the 12 high-risk HPV (hrHPV) types 16/18/31/33/35/39/45/51/52/56/58/59. We compared hrHPV positivity between self-reported vaccinated (≥1 dose) and unvaccinated women, and estimated VE by a logistic mixed model. Results: We included 1087 women of which 53% were hrHPV positive and 60% reported to be vaccinated. The adjusted pooled VE against HPV-16/18 was 89.9% (81.7%–94.4%). Moreover, we calculated significant VE against nonvaccine types HPV-45 (91%), HPV-35 (57%), HPV-31 (50%), and HPV-52 (37%). Among women who were offered vaccination 5/6 years ago, we estimated similar VE against HPV-16/18 (92%) and all hrHPV types (35%) compared to women who were offered vaccination <5 years ago (83% and 33%, respectively). Conclusion: We demonstrated high VE of the bivalent vaccine against HPV-16/18 and cross-protection against HPV-45/35/31/52. Protection against HPV-16/18 was sustained up to 6 years postvaccination.